2018
DOI: 10.1002/jcp.27133
|View full text |Cite
|
Sign up to set email alerts
|

KRT1 gene silencing ameliorates myocardial ischemia–reperfusion injury via the activation of the Notch signaling pathway in mouse models

Abstract: Myocardial ischemia and reperfusion injury (MIRI) includes major drawbacks, such as excessive formation of free radicals and also overload of calcium, which lead to cell death, tissue scarring, and remodeling. The current study aims to explore whether KRT1 silencing may ameliorate MIRI via the Notch signaling pathway in mouse models. Myocardial tissues were used for the determination of the positive rate of KRT1 protein expression, apoptosis of myocardial cells, creatine kinase (CK) and lactate dehydrogenase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…23 Research has shown that the miR-21/ TLR4/NF-jB pathway takes part in myocardial apoptosis in rats with myocardial ischemia-reperfusion. 24 The current study demonstrated that the levels of miR-21 mRNA were significantly increased as a result of ischaemia-reperfusion in rats and treatment with curcumin reduced the levels of miR-21 mRNA. In addition, the concomitant administration of an inhibitor of miR-21 (antagomir-21) resulted in increased levels of miR-21 mRNA.…”
Section: Discussionmentioning
confidence: 48%
“…23 Research has shown that the miR-21/ TLR4/NF-jB pathway takes part in myocardial apoptosis in rats with myocardial ischemia-reperfusion. 24 The current study demonstrated that the levels of miR-21 mRNA were significantly increased as a result of ischaemia-reperfusion in rats and treatment with curcumin reduced the levels of miR-21 mRNA. In addition, the concomitant administration of an inhibitor of miR-21 (antagomir-21) resulted in increased levels of miR-21 mRNA.…”
Section: Discussionmentioning
confidence: 48%
“…Additionally, the cell components were mainly concentrated in the nucleus, and molecular functions were primarily concentrated on protein binding (Figure b). Subsequently, KRT1 was found to exert regulatory effect through the Notch signaling pathway (Fang et al, ; Gao et al, ). Immunohistochemistry results displayed that KRT1 expression was evidently upregulated in renal epithelial cells of uremic rats in relation to the sham‐operated rats.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, by interacting with the vascular endothelial growth factor pathway, the Notch pathway, whose inactivation serves as a therapeutic insight for diabetic nephropathy treatment, could enhance diabetic kidney disease progression (Seon‐Ho & Katalin, ). Based on the current literature (Fang et al, ; Gao et al, ), which demonstrated that KRT1 has been involved in the Notch signaling pathway, it was hypothesized that KRT1 has the potential to regulate the Notch pathway to affect glomerulosclerosis and kidney dysfunction. In conclusion, in this study, the physiological role of KRT1 silencing and Notch pathway inhibition in uremia was investigated by regulating glomerulosclerosis and kidney dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Keratin family proteins can promote the proliferation of epithelial cells via multiple immune response pathways, and the epidermal cells are known to serve a key role in airway remodeling during asthma (23). Previous research has indicated that KrT1 was involved in the regulation of the notch signaling pathway and affected the repair of vascular endothelial cell damage (24,25). It has been identified that the specific expression of KRT1 affects complex traits (26).…”
Section: Discussionmentioning
confidence: 99%